Prediction of metabolic activity of rowing athletes based on serum biochemical analysis - Pustovoyt, V. I.; Astrelina, T. A.; Balakin, E. I.; Kobzeva, I. V.; Suchkova, Y. B.; Khan, A. V.; Murtazin, A. A.; Maksjutov, N. F.; Brumberg, V. A. (Biofizika, 2023)
Determination of the metabolic state is an important topic in sports medicine. Biochemical and hematological blood parameters reflect the predominance of anabolic or catabolic processes in metabolism, these parameters depend on intensity and duration of workouts. The aim of the present study was to determine whether metabolic processes are dominant. 21 male rowing athletes (age: 22.55 ± 3.68 years, height: 189.62 ± 6.34 cm, weight: 88.65 ± 8.55 kg) participated in the experiment. Monitoring of blood concentrations in samples collected from participating athletes and measuring workout intensity led to the use of a linear-discriminant function. With this technique, the eight main blood count parameters: creatinine (p < 0.001), uric acid (p < 0.001), urea (p < 0.001), testosterone (p < 0.001), ALP (p < 0.001), albumin (p < 0.05), total calcium (p < 0.05), and total protein (p < 0.05) for the prediction of the metabolic state have been determined. The reliability of test results using a linear-discriminant function for the prediction of the metabolic state in athletes was supported by a strong positive correlation (r = 0.88, p < 0.001) with the results of the neuroendocrine system activity assessments. The accuracy of the metabolic state prediction was 91.8%.